DESARROLLO DE UN ÍNDICE DE CONDICIÓN CORPORAL EN CUYES: RELACIONES ENTRE CONDICIÓN CORPORAL Y ESTIMADOS CUANTITATIVOS DE GRASA CORPORAL. - Ara G., Miguel (2012)
The purpose of the study was to strengthen the development and validation of a body condition score (BCS) system for guinea pigs of the IVITA Research Centre, measuring its consistency among evaluators and its ability to predict fat changes. Forty Peru female guinea pigs were under feed restriction for four weeks to obtain animals in each unit of the BCS. Four technicians evaluated each animal in a 1 to 5 rating system, with 0.5 increments (1 = emaciated, 5 = obese). Then, the animals were weighed and measured to obtain the body mass index (BMI) and slaughtered to obtain the gravimetric mass of the mesenteric, perirenal-uterine, dorso-cervical-caudal, mammary, popliteal, and axilar fat deposits. The inter-rater reliability was assessed by the intraclass correlation coefficient (ICC); the association between BCS and nine quantitative estimates of body fat was measured through correlation analysis; and the ability to predict variations in the quantitative fat was measured through regression analysis. The BCS showed a good inter-rater reliability (CCI = 0.77), and its values were significantly correlated with all body fat estimates; however, the highest coefficients were obtained for IMC (0.87), total fat (0.83) and dorso-cervical-caudal fat (0.86). Each unit increment in BCS resulted in an increment of 0.17 ± 0.032 in BMI, 62.78 ± 13.21 g in total fat, and 8.03 ± 1.46 g in dorsocervical- caudal fat. These results suggest that the IVITA BCS system is a promissory management technique in terms of its consistency, good association with quantitative body fat and its ability to predict fat changes in guinea pigs.